The effect of online customer review, electronic word of mouth, and product quality on purchase decisions for Galeri 24 precious-metal products at Pegadaian UPC Kartini Kisaran - Erika Fadilah; Tengku Syarifah (Privietlab, 2026)
The accelerating digitalization of retail gold investment has made consumer-generated online information an increasingly visible part of the purchase environment; however, its role in high-involvement, standardized products such as certified precious metals remains under-examined. This study investigates the predictive relationships between online customer reviews, electronic Word-of-Mouth (e-WOM), and product quality with the purchase decision for Galeri 24 precious-metal products at Pegadaian UPC Kartini Kisaran, Indonesia. A quantitative associative cross-sectional survey design was employed. Primary data were collected using a five-point Likert questionnaire administered to 96 customers who purchased Galeri 24 gold, selected by purposive sampling with the sample size determined using the Cochran formula for an unknown population. The respondent profile was dominated by women (79.2%), respondents aged 31-50 years (51.0%), and employees or self-employed respondents. Data were analyzed using multiple linear regression after validity, reliability, classical assumption, common method, and correlation checks. The three predictors jointly explained 54.3% of the variance in purchase decisions, F(3, 92) = 36.426, p < .001. However, the partial pattern was more nuanced: product quality showed a strong and statistically significant positive relationship (β = .489, p < .001), whereas online customer reviews (β = .180, p = .058) and e-WOM (β = .166, p = .071) showed positive but statistically non-significant relationships at the 5% level. Therefore, the results should be interpreted as perceived/predictive associations, not as strict causal effects. The theoretical and managerial implications for Pegadaian and digital gold-investment marketing are discussed.